A carbon efficiency evaluation method for manufacturing process chain decision-making. (1st April 2017) - Zhu, Shuo; Jiang, Zhigang; Zhang, Hua; Tian, Guangdong; Wang, Yanan
Abstract: Low carbon manufacturing (LCM) is increasingly being regarded as the direction for technological innovation and implementation in industry. The manufacturing process chain plays a critical role in LCM to consider and define the whole production process, thus the analysis and evaluation method for its decision-making is urgently needed. Although interest in addressing carbon emission reduction in manufacturing is rising, the study of incorporating carbon emission reduction and economic improvement into the process chain is still considerably deficient. This work proposes a novel method to identify a process chain with the optimal carbon efficiency, where the carbon efficiency of process chain (CEpc) regarded as an effective indicator is evaluated by manufacturing value and carbon emissions defined based on eco-efficiency. In addition, the estimation models of manufacturing value and carbon emission are proposed, based on which, a decision-making model is established to solve the process chain decision-making issues with objective to maximize CEpc. An illustrative example of the sleeve part manufacturing process is conducted to demonstrate the effectiveness of this method. And the outcome can help decision makers to select the process chain with optimal carbon efficiency based on the dynamic change of production and different processing conditions. Furthermore, sensitivity analysis on material utilization rate, recycling rate as well as processing efficiency is presented to reveal the impacts of relevant improvement measures in CEpc for manufacturers.